Experimental Investigation on Reduction of High Combined Water Contained Iron Ore by Ammonia-Methane-Mixed Gas - Kurniawan, Ade; Iwamoto, Itsuki; Kashiwaya, Yoshiaki; Nomura, Takahiro (Universitas Negeri Semarang, 2024)
Reducing CO₂ emissions in the steel industry, which contributes 7% of global emissions, is crucial. Ammonia, as a hydrogen-based reducing agent offers one promising solution to address the decarbonization challenge in primary ironmaking process due to its high hydrogen storage density and ease of transport. However, for subsequent steelmaking process, the lack of carbon in the reduced ore from the ammonia-hydrogen iron reduction system must be addressed. In this study, we reduced iron ore using an ammonia-methane mixed reducing gas to introduce carbon into the reduced ore, from the raw material of porous ore prepared from a high combined water, goethite ore. We varied the reduction conditions to investigate how the reaction and carbon content would change, aiming to optimize the reduction process and enhance carbon content in the reduced iron. The results show that ammonia is primarily consumed for iron reduction, facilitated by hydrogen from its decomposition, while methane decomposes into carbon and hydrogen. Methane decomposition begins around 800°C, significantly increasing the ore's carbon content. Higher temperatures accelerate both reduction and carbon incorporation. The ammonia-methane mixing ratio influences reduction efficiency and carbon content, with a higher ammonia ratio expediting these processes. At 850°C, a 1:1 ammonia-methane mixture yields higher carbon content than higher ammonia ratios. This study highlights the potential of ammonia-methane mixed gases for sustainable steel production by enhancing the reduction and carbonization of high-CW-content iron ores.